Mangrove and Tsunami: Between Myth and Reality - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
Abstract A lot of discussion has been generated on the role and effectiveness of mangrove on the aftermath of the destructive tsunami tragedy of December 26, 2005. Most pointed to the effect of mangrove in breaking the waves of tsunami rendering less casualties along the coastal areas. The characteristics of the mangrove ecosystem to an extent help to diffuse the impact of the tsunami. However, certain issues goes with the reality in creating the buffer against tsunami. This paper discuss the myth and reality of the impact of tsunami by the mangrove forest